Feasibility study of an online toxicological sensor based on the optical waveguide technique - Vörös, J.; Graf, R.; Kenausis, G.L.; Bruinink, A.; Mayer, J.; Textor, M.; Wintermantel, E.; Spencer, N.D. (Biosensors & bioelectronics, 2000)
Morphological properties of the cells often change as an early response to the presence of a pharmacologically acting toxic substance [Etcheverry, S.B., Crans, D.C., Keramidas, A.D., Cortizo, A.M., Arch. Biochem. Biophys. 338 (1997) 7–14]. Recently it has been shown that living animal cell adhesion and spreading can be monitored online and quantitatively via the interaction of the cells with the evanescent electromagnetic field present at the surface of an optical waveguide [Ramsden, J.J., Li, S.Y., Heinzle, E., Prinosil, J.E. Cytometry 19 (1995) 97–102]. In the present study, optical waveguide lightmode spectroscopy (OWLS) and confocal laser scanning microscopy (CLSM), which provides information about the shape of the cells at the surface, were compared under identical experimental conditions. This allowed for the correlation between the cell-shape information from CLSM and the cell-surface interaction measurements from OWLS. The proposed design of the microsystem sensor involves the establishment of a cell layer on the surface of the waveguide and the subsequent online measurement of the morphological response of the cells to various toxic substances. In the present study, the setup was evaluated using cells from an osteoblastic MC 3T3-E1 cell line, and sodium hypochlorite was used as model toxic substance. Comparing the OWLS signal to the morphological response measured by CLSM reveals that OWLS is effective in monitoring not only cell attachment and spreading but also the cellular response to toxic compounds (i.e. by means of change in cell morphology). For the model toxin, the OWLS measurements indicate that, at concentrations above 0.01%, the cells exhibit a clearly discernable morphological effect (i.e. a decrease in average cell contact area). Thus, the potential of an on-line sensor based on OWLS to applications in toxicology, pharmacy and biocompatibility was demonstrated.